Kinetics of the reaction between elemental sulfur and silver in synthetic esters and comparison with mineral oils - Djukic, Milica; Lukic, Jelena; Jankovic, Jelena; Kolarski, Dejan (Proceedings, Electrical engineering institute "Nikola Tesla", 2025)
For decades, the problem of corrosive sulfur was considered to be exclusively associated with mineral oils. However, recent cases from industry have disproved this assumption. The presence of elemental sulfur in insulating oil causes corrosion of silver contacts and consequently leads to power transformer failures. The aim of this study is to determine the kinetics of the reaction between elemental sulfur and silver in synthetic ester within the temperature range of 120–180 °C. The elemental sulfur content in the oil during the reaction is determined using gas chromatography with an electron capture detector (GC-ECD). The results show that the reaction between silver and elemental sulfur follows the first-order law. A comparative analysis of the examined reaction in synthetic ester and mineral oil shows that the reaction proceeds faster in synthetic ester.